Biodegradable nanocomposite films based on sodium alginate and cellulose nanofibrils - Deepa, B. (2021)
Biodegradable nanocomposite films were prepared by incorporation of cellulose nanofibrils (CNF) into alginate biopolymer using the solution casting method. The effects of CNF content (2.5, 5, 7.5, 10 and 15 wt %) on mechanical, biodegradability and swelling behavior of the nanocomposite films were determined. The results showed that the tensile modulus value of the nanocomposite films increased from 308 to 1403 MPa with increasing CNF content from 0% to 10%; however, it decreased with further increase of the filler content. Incorporation of CNF also significantly reduced the swelling percentage and water solubility of alginate-based films, with the lower values found for 10 wt % in CNF. Biodegradation studies of the films in soil confirmed that the biodegradation time of alginate/CNF films greatly depends on the CNF content. The results evidence that the stronger intermolecular interaction and molecular compatibility between alginate and CNF components was at 10 wt % in CNF alginate films.